Q&A: ICTs and land valuation services in Jamaica - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Knowing the exact value of a piece of land is essential both for local governments, to enable them to levy appropriate taxes, and for farmers to calculate their annual budgets. Yet in order to establish the value of land, both parties often have to find t